Angka Kejadian Stunting Pada Bayi dan Balita - Hatijar Hatijar (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The incidence of short toddlers, or stunting, is a condition where toddlers have less height than their age. This condition is measured by length or height, which is less than minus two standard deviations of the WHO child growth standard median. This research aims to describe the incidence of stunting in infants and toddlers in the workplace. Research Method: This research is descriptive research with a retrospective approach. The population in the study were all children under five, with a total of 1297 people, and the sample was children under five who experienced stunting, as many as 126 people. The sampling technique in this study was a purposive sample using secondary data processed manually using a calculator and presented in the form of a frequency distribution table. Results of the study: The frequency of stunting incidents based on age that experienced the most stunting was 60 people (47.7%) aged 24-59 months, 80 people (63.4%) male sex, 108 short height people (85.8%). Conclusion: From the study results, it can be concluded that the most stunting incidents were from ages 24-59 months, male sex, and short height